MnTe semiconductor-sensitized boron-doped TiO2 and ZnO photoelectrodes for solar cell applications - Tubtimtae A. (2014)
We report a new tailoring MnTe semiconductor-sensitized solar cells (MnTe SSCs) using successive ionic layer adsorption and reaction (SILAR) technique. X-ray diffraction and SAED patterns reveal the orthorhombic MnTe and cubic MnTe2 phases were grown on boron-doped TiO2 and ZnO nanoparticles. The diameter of MnTe NPs ranged from 15 to 30nm on both B-doped metal oxide structures. The energy gaps of metal oxide become narrower after boron doping, which have an advantage for enhancing the light absorption from UV to visible region. Also, the energy gap of MnTe NPs on B-doped metal oxide was determined ~1.27-1.30eV. The best power conversion efficiency (η) of 0.033% and 0.030% yielded from B-doped TiO2/MnTe(7) and B-doped ZnO/MnTe(9), respectively. The reduction in power conversion efficiency by 103% and 91% was due to the absence of boron doping into TiO2 and ZnO nanostructures, respectively. © 2013.